Análise das Cortes Constitucionais em o contexto do common e civil law e a influência política em suas deliberações - Capelari, Bruna (2015)
This work aims the analysis of eventual political influence exercised in the deliberations of constitutional Courts in common and civil law systems due to the form of investiture of its members and especially the majority share of political bodies in this procedure which is assigned the function of raising to power the members who compose it, justifying such research due to the own e. Supremo Tribunal Federal - STF , the highest Court of the Brazilian Judiciary, be the subject of reflections on the theme, especially given the form of investiture of its members, in addition to treating the subject of relevant theme from an academic point of view. For the development of work towards your outcome readings were performed, research and reflections on the relevant legal provisions inserted in the Brazilian Federal Constitution and the Fundamental Laws of sovereign States here invoked and linked to the common and civil law systems, having being also performed research in the national and foreign doctrine in order to enrich the work and give a personal touch to each of the analyzed States by evocation of scholars that they are linked by bonds of nationality